Acute Kidney Injury Secondary to Trauma Brain Injury (TBI) and the Role of Angiotensin-1-7 - Mehdi Jahantigh; Abolfazl Parsi-Moud; Hamede Damani; Mohammad Ali Mirshekar; Ilia Mirzaei; Hossein Bagheri; Elham Shoghi; Tahereh Safari (Advanced Biomedical Research)
Background: Acute kidney injury (AKI) following traumatic brain injury (TBI) can highly influence the patient’s outcomes. The involvement of the renin-angiotensin system (RAS) and Angiotensin II (Ang-II) in inducing renal injury after stroke has been reported in different studies. This study evaluated, TBI’s impact on kidney function/structure and the therapeutic potential of Angiotensin-1-7 (Ang-1-7). Materials and Methods: Thirty-two male Wistar rats were randomly assigned to four experimental groups including: Vehicle, TBI, Ang-1-7, and TBI+ Ang-1-7. Then blood urea nitrogen (BUN), creatinine (Cr), malondialdehyde (MDA), nitrite, and renal damage, based on the kidney tissue damage score (KTDS), were evaluated. Results: Traumatic brain injury induced significant renal dysfunction, evidenced by elevation in serum Cr levels in TBI group compared to vehicle group, P<0.05. Notably, this functional impairment occurred without observable histopathological damage in renal tissue sections stained with H&E. Therapeutic administration of Ang-1-7 post-TBI attenuated these effects in TBI+Ang-1-7 group, reducing Cr levels P<0.05. The treatment concurrently decreased oxidative stress, with (MDA) concentrations in TBI+Ang-1-7 group compared to TBI group. However, no significant differences were detected in serum BUN levels across experimental groups. Conclusion: TBI causes functional but not structural renal impairment, reversible with Ang-1-7 via Mas receptor activation.